2022
DOI: 10.1126/sciadv.add0510
|View full text |Cite
|
Sign up to set email alerts
|

The void formation behaviors in working solid-state Li metal batteries

Abstract: The fundamental understanding of the elusive evolution behavior of the buried solid-solid interfaces is the major barrier to exploring solid-state electrochemical devices. Here, we uncover the interfacial void evolution principles in solid-state batteries, build a solid-state void nucleation and growth model, and make an analogy with the bubble formation in liquid phases. In solid-state lithium metal batteries, the lithium stripping–induced interfacial void formation determines the morphological instabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…Solid‐state lithium metal batteries (SSLMBs) are highly desirable for electrochemical energy storage because of the urgent need for higher energy density and safer battery application such as electric vehicles, portable devices, and energy storage power stations. [ 1–7 ] To achieve more competitive battery technology, excellent high‐power cycling, and low‐temperature operation performance are desired for SSLMBs. [ 8–10 ] The solid‐state electrolyte is one of the key components of SSLMBs, which acts as the ion transport pathway and is also critical to SSLMBs performance.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐state lithium metal batteries (SSLMBs) are highly desirable for electrochemical energy storage because of the urgent need for higher energy density and safer battery application such as electric vehicles, portable devices, and energy storage power stations. [ 1–7 ] To achieve more competitive battery technology, excellent high‐power cycling, and low‐temperature operation performance are desired for SSLMBs. [ 8–10 ] The solid‐state electrolyte is one of the key components of SSLMBs, which acts as the ion transport pathway and is also critical to SSLMBs performance.…”
Section: Introductionmentioning
confidence: 99%
“…This research revealed how the interaction of void formation, interphase growth and volume change affect on the cell operating mechanism, notably, they found that the local interface roughness does not affect the tendency of void formation during the stripping process. Lu et al 97 investigated the interfacial Li void formation and evolution mechanism by comparing the Li void behaviors in solid‐state batteries to the bubble production processes in liquid phases, while the void was considered as bubbles and Li metal was treated as solution. Their research indicates that due to the intrinsic void diffusion, the voids formed at the interface will spread into the bulk of Li anode, while the diffusion coefficient can be considered as “floating rate” in the liquid phase.…”
Section: Interfacial Property Engineeringmentioning
confidence: 99%
“…Experimentally, the formation of voids can be followed electrochemically due to the associated increase in interfacial resistance (constriction resistance) [33] . This constriction resistance can be minimized by controlling the mechanical properties of the alkali metal through optimization of external parameters such at temperature and pressure [33,112,114,115] …”
Section: The Theory Of Wettingmentioning
confidence: 99%